Dampak Harga dan Citra Merek terhadap Minat Beli Ulang yang Dimediasi oleh Kepuasan Pelanggan pada Produk Sabun Mandi Batang Merek Lifebuoy di Kota Bandung - Azhari, Anisa Listia; Putra, Hariyadi Triwahyu (Journal of Management and Bussines (JOMB), 2024)
This study aims to analyze the effect of price and brand image on repurchase intention of Lifebuoy brand bath soap products in Bandung City, with customer satisfaction as a mediating variable. Data were collected through instruments that had been tested for reliability and validity, with a sample of 120 respondents who had used the product. The sampling technique used was purposive sampling, and this study used a cross-sectional approach. Data analysis was carried out using descriptive test methods and multiple linear regression using SPSS version 23, as well as the Sobel test to test mediation. The results showed that price and brand image significantly influenced repurchase intention, and customer satisfaction acted as a mediator in the relationship. In conclusion, this study provides new insights related to the factors that influence repurchase intention, especially in the context of Lifebuoy bath soap bars in Bandung City, and is expected to be a reference for managers in designing more effective marketing strategies. Keywords: Price, Brand Image, Customer Satisfaction, Repurchase Intention